Regulation of the Phytoplankton Heme b Iron Pool During the North Atlantic Spring Bloom - Louropoulou, Evangelia; Gledhill, Martha; Browningi, Thomas J.; Desai, Dhwani K.; Barraqueta, Jan-lukas Menzel; Tonnard, Manon; Sarthou, Geraldine; Planquette, Helene; Bowie, Andrew R.; Schmitz, Ruth A.; Laroche, Julie; Achterberg, Eric P. (Frontiers in Microbiology, 2019)
Heme b is an iron-containing co-factor in hemoproteins. Heme b concentrations are low (< 1 pmol L-1) in iron limited phytoplankton in cultures and in the field. Here, we determined heme b in marine particulate material (> 0.7 mu m) from the North Atlantic Ocean (GEOVIDE cruise - GEOTRACES section GA01), which spanned several biogeochemical regimes. We examined the relationship between heme b abundance and the microbial community composition, and its utility for mapping iron limited phytoplankton. Heme b concentrations ranged from 0.16 to 5.1 pmol L-1 (median = 2.0 pmol L-1, n = 62) in the surface mixed layer (SML) along the cruise track, driven mainly by variability in biomass. However, in the Irminger Basin, the lowest heme b levels (SML: median = 0.53 pmol L-1, n = 12) were observed, whilst the biomass was highest (particulate organic carbon, median = 14.2 mu mol L-1, n = 25; chlorophyll a: median = 2.0 nmol L-1, n = 23) pointing to regulatory mechanisms of the heme b pool for growth conservation. Dissolved iron (DFe) was not depleted (SML: median = 0.38 nmol L-1, n = 11) in the Irminger Basin, but large diatoms (Rhizosolenia sp.) dominated. Hence, heme b depletion and regulation is likely to occur during bloom progression when phytoplankton class-dependent absolute iron requirements exceed the available ambient concentration of DFe. Furthermore, high heme b concentrations found in the Iceland Basin and Labrador Sea (median = 3.4 pmol L-1, n = 20), despite having similar DFe concentrations to the Irminger Basin, were attributed to an earlier growth phase of the extant phytoplankton populations. Thus, heme b provides a snapshot of the cellular activity in situ and could both be used as indicator of iron limitation and contribute to understanding phytoplankton adaptation mechanisms to changing iron supplies.